"Coming Out" of Prison: An Exploratory Study of LGBT Elders in the Criminal Justice System. Issue 9 (1st September 2016) - Maschi, Tina; Rees, Jo; Klein, Eileen
ABSTRACT: This two-phase qualitative study explores the experiences of 10 formerly incarcerated LGBT elders' experiences prior to, during, and after release from prison. A core theme of self and the social mirror emerged from the data that represented LGBT elders ongoing coming-out process of unearthing their "true selves" despite managing multiple stigmatized identities or social locations, such as being LGBT, elderly, HIV positive, formerly incarcerated, and a racial/ethnic minority. These findings further our awareness of an overlooked population of LGBT who are older and involved in the criminal justice system. Recommendations that incorporate suggestions from formerly incarcerated LGBT elders for services and policy reform are presented.